PERTIMBANGAN PUTUSAN PENGENAAN DENDA DALAM PELANGGARAN LALU LINTAS JALAN RAYA - Bayu Apriliyantomo (Universitas Islam Darul Ulum, 2020)
Traffic violations on the highway by motorists lead to accidents. The majority of traffic violations are in the form of violations of traffic signs, such as prohibitions on stopping and parking in certain places, violating traffic lights such as breaking through red lights, and others. Inspections of motorized vehicles on the road by police officers or police operations are in fact law enforcement officers who provide more criminal sanctions in the form of fines than imprisonment (imprisonment) for motorists who violate traffic regulations. The research method used is a normative legal research method through a statute approach and a conceptual approach to the decision to impose fines in road traffic violations according to Law No. 22 of 2009 concerning Road Traffic and Transportation. In deciding the case of traffic violations, the Judge in considering his decision is faced with two choices to decide the case, namely whether to decide to impose a maximum imprisonment of 2 (two) months or decide to impose a fine. In practice, judges choose a second alternative decision, which is to impose fines on violators. The legal basis and considerations are Article 7 paragraph (2) of the Regulation of the Supreme Court (PERMA) Number 12 of 2016 concerning Procedures for the Settlement of Traffic Violation Cases.